HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN DIET PADA PASIEN HIPERTENSI: SUATU LITERATURE REVIEW - Adzra, Syaharani (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2025)
Hypertension is one of the most significant global health problems and is widely recognized as the silent killer due to its asymptomatic nature and its potential to cause severe complications, including coronary heart disease, kidney failure, and stroke if not properly managed. Adherence to a hypertension diet is a key component of effective blood pressure control and is influenced by several factors, particularly family support. This study aimed to examine the relationship between family support and dietary adherence among patients with hypertension using a literature review approach. A literature search was conducted through the Google Scholar database using the keywords family support, dietary adherence, and hypertension. Indonesian-language articles published between 2017 and 2024 that met the predetermined inclusion criteria were included in the review. A total of 15 eligible articles were analyzed. The findings revealed that 11 studies reported a positive relationship between family support and adherence to a hypertension diet. Emotional, informational, instrumental, and appraisal support provided by family members enhanced patients' motivation to comply with dietary recommendations. Conversely, four studies indicated that inadequate family support was associated with lower levels of dietary adherence. In conclusion, family support plays a crucial role in improving dietary adherence among patients with hypertension and should be strengthened through family-centered education and hypertension management programs.